2018
DOI: 10.3892/etm.2018.7066
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic abdominal aortic balloon occlusion: An effective method of controlling hemorrhage in patients with placenta previa or accreta

Abstract: Postpartum hemorrhage is considered to be a serious complication in patients with pernicious placenta. Approaches employing abdominal aortic balloon occlusion to control hemorrhage are extremely effective for such patients. The present study analyzed 9 patients with pernicious placenta previa in a single hospital from June 2016 to November 2017. Prior to cesarean hysterectomy, an abdominal aortic balloon catheter was placed in all patients. The balloon was inflated and evacuated alternately using saline follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…The complications after vascular embolisation also remain controversial and may include ischaemic necrosis of the lower limbs, thrombosis of the internal iliac artery, haematoma at the puncture site, ischaemia-reperfusion injury of tissues and organs and acute renal failure, among others. Iliac artery thrombosis has been reported to be the most common complication, with a risk of approximately 5% [44,46,47], which may be due to changes in maternal blood flow, vascular injury during puncture and the hypercoagulable state of blood during pregnancy [46]. One patient developed lower limb thrombosis on the first day after balloon occlusion of the internal iliac artery in our hospital after internal iliac artery embolisation.…”
Section: Discussionmentioning
confidence: 88%
“…The complications after vascular embolisation also remain controversial and may include ischaemic necrosis of the lower limbs, thrombosis of the internal iliac artery, haematoma at the puncture site, ischaemia-reperfusion injury of tissues and organs and acute renal failure, among others. Iliac artery thrombosis has been reported to be the most common complication, with a risk of approximately 5% [44,46,47], which may be due to changes in maternal blood flow, vascular injury during puncture and the hypercoagulable state of blood during pregnancy [46]. One patient developed lower limb thrombosis on the first day after balloon occlusion of the internal iliac artery in our hospital after internal iliac artery embolisation.…”
Section: Discussionmentioning
confidence: 88%
“…It may cause complications, including initial vessel injury, arterial thrombosis, puncture point haematoma, ischaemic necrosis of the lower limbs, reperfusion injury of tissues and organs, acute renal failure and rarely artery rupture [ 10 – 12 , 28 ]. It was reported that measurement of the abdominal aortic diameter before the intervention, clearance of the opening of the renal artery and control of the duration of balloon occlusion are essential for decreasing the risk of complications [ 29 ]. In our study, the diameter of the abdominal aorta was measured by MRI before surgery to determine the appropriate size of the balloon catheter.…”
Section: Discussionmentioning
confidence: 99%
“…34,35 In our study there were no apparent complications resulting directly from the use of occlusive balloons, although we note that there have Original Research been previous reports of ischemic necrosis of the lower limbs, arterial thrombosis, and initial vessel injury secondary to balloon placement. 36,37 Results in the context of prior studies…”
Section: Principal Findingsmentioning
confidence: 96%